2007
DOI: 10.1038/sj.tpj.6500457
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary risk information and pharmacogenetic tests: social and policy implications

Abstract: Some pharmacogenetic tests may provide ancillary disease risk information. To evaluate evidence and assess the social and policy implications of ancillary disease risk information associated with candidate pharmacogenetic variants, We conducted a literature search and abstract review of disease susceptibility studies for each of 42 gene variants potentially associated with drug response. Twenty-two variants (53%) had suggested association with disease risk in at least two studies, and sixteen (38%) were for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Other emerging issues which are not mentioned by the respondents0 but are a source of ethical debate in the literature and the guidelines include compensation of the participants [16, 17], storage and destruction of data after completion of the study [43], future research use of the collected samples, policy on the communication of research results [19, 44], identification of sources of funding, and the possibility of commercialization of the results [16, 17]. From an ethical point of view, there is a need to think about these issues when addressing the informed consent [45].…”
Section: Discussionmentioning
confidence: 99%
“…Other emerging issues which are not mentioned by the respondents0 but are a source of ethical debate in the literature and the guidelines include compensation of the participants [16, 17], storage and destruction of data after completion of the study [43], future research use of the collected samples, policy on the communication of research results [19, 44], identification of sources of funding, and the possibility of commercialization of the results [16, 17]. From an ethical point of view, there is a need to think about these issues when addressing the informed consent [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pharmacogenomic testing may provide ancillary disease risk information, which might affect the ability of patients to obtain secure life insurance/protection [55]. The psychological burden to both children and parents should also be considered, because ancillary disease risk information implies the potential development of one or more diseases.…”
Section: Ethical Concerns In Paediatricsmentioning
confidence: 99%
“…However, one study reported more than a third of the 42 inherited pharmacogenetic variants reviewed were associated with a disease unrelated to the pharmacogenetic indication. 30 The greatest risk of ancillary information will likely occur with a prospective pharmacogenetic profile. This testing approach involves measurement of many gene variants to inform future treatment decisions, amplifying the potential for ancillary risk information.…”
Section: Ancillary Informationmentioning
confidence: 99%